Energy Storage - Islam Sheikh, Rafiqul (IntechOpen, 2010)
Electricity is more versatile in use because it is a highly ordered form of energy that can be converted efficiently into other forms. However, the disadvantage of electricity is that it cannot be easily stored on a large scale. One of the distinctive characteristics of the electric power sector is that the amount of electricity that can be generated is relatively fixed over short periods of time, although demand for electricity fluctuates throughout the day. Almost all electrical energy used today is consumed as it is generated. This poses no hardship in conventional power plants, where the fuel consumption is varied with the load requirements. However, the photovoltaic and wind, being intermittent sources of power, cannot meet the load demand all of the time. Wherever intermittent power sources reach high levels of grid penetration, energy storage becomes one option to provide reliable energy supplies. These devices can help to make renewable energy more smooth and reliable, though the power output cannot be controlled by the grid operators. They can balance micro grids to achieve a good match between generation and load demand, which can further regulate the voltage and frequency. Also, it can significantly improve the load availability, a key requirement for any power system. The energy storage, therefore, is a desired feature to incorporate with renewable power systems, particularly in stand alone power plants. The purpose of this book is twofold. At first, for the interested researcher it shows the importance of different Energy Storage devices, but secondly, and more importantly, it forms a first attempt at dissemination of knowledge to the wider non-expert community who may wish to consider Energy Storage device for specific application. Thus this book will be helpful to provide an indication of the tools necessary for an assessment to be made Energy Storage device more powerful.